2021
DOI: 10.1016/j.redox.2021.102120
|View full text |Cite
|
Sign up to set email alerts
|

Irisin ameliorates doxorubicin-induced cardiac perivascular fibrosis through inhibiting endothelial-to-mesenchymal transition by regulating ROS accumulation and autophagy disorder in endothelial cells

Abstract: The dose-dependent toxicity to cardiomyocytes has been well recognized as a central characteristic of doxorubicin (DOX)-induced cardiotoxicity (DIC), however, the pathogenesis of DIC in the cardiac microenvironment remains elusive. Irisin is a new hormone-like myokine released into the circulation in response to exercise with distinct functions in regulating apoptosis, inflammation, and oxidative stress. Recent advances revealed the role of irisin as a novel therapeutic method and an important mediator of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(52 citation statements)
references
References 53 publications
0
52
0
Order By: Relevance
“…Neonatal mouse ventricular myocytes (NMVMs) were isolated from one-day old C57BL/6 J pups as previously described [ 27 ]. More than 95% of cardiomyocytes are typically present in cell preparations.…”
Section: Methodsmentioning
confidence: 99%
“…Neonatal mouse ventricular myocytes (NMVMs) were isolated from one-day old C57BL/6 J pups as previously described [ 27 ]. More than 95% of cardiomyocytes are typically present in cell preparations.…”
Section: Methodsmentioning
confidence: 99%
“…Although activated fibroblasts, named myofibroblasts, are regarded as the predominant regulator for fibrosis, the contribution of EndMT to the initiation and progression of fibrosis has been gradually appreciated [164,165]. Recent research suggests that the inhibition of autophagy to EndMT serves as a critical cardioprotective mechanism in ameliorating cardiac fibrosis [149,150,[166][167][168]. According to Ke's study, restoring the TFEB-mediated autophagic flux could inhibit the transforming growth factor-β (TGF-β)-meditated EndMT and promote angiogenesis in HCAECs by triggering TFEB nucleus translocation [166].…”
Section: The Role Of Autophagy In Endothelial-mesenchymal Transition ...mentioning
confidence: 99%
“…In addition, the upregulation of autophagy was reported to prevent hypoxia-induced EndMT and cell apoptosis, while enhancing angiogenesis by inhibiting the NF-κB-Snail signaling pathway in human CMECs [149,150]. Furthermore, Pan et al identified that irisin (a new hormone-like myokine, primarily secreted by cardiomyocytes) treatment significantly alleviated doxorubicin-initiated cardiac perivascular fibrosis by restraining EndMT via restoring autophagy in ECs, resulting in reduced ROS accumulation and inhibited NF-κB-Snail pathway [168]. However, some researchers found that in certain conditions, the activation of autophagy could induce EndMT and contribute to cardiac fibrosis [169,170].…”
Section: The Role Of Autophagy In Endothelial-mesenchymal Transition ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Mice transverse aortic constriction (TAC)-induced cardiac hypertrophy model reported irisin treatment attenuates pressure overload-induced cardiac hypertrophy and fibrosis mainly through regulating AMPK-mTOR signaling or inhibiting NOD-like receptor protein 3 (NLRP3) -mediated pyroptosis activation (Yu et al, 2019;Yue et al, 2021). A recent study revealed that irisin as a mediator of the beneficial effects of exercise in cardioprotection like ameliorate EndMT through inhibiting activation of NF-κB-Snail pathway due to excessive accumulation of UCP2 and ROS and regulating the autophagy disorders (Pan et al, 2021). In summary, these findings show that irisin (including exercise-induced irisin secretion) exerts a myocardial protective role through its anti-inflammation activity, antioxidant stress effect, and anti-apoptosis properties, as well as improving mitochondrial function, promoting angiogenesis and fibrotic remodeling.…”
Section: Anti-fibrosismentioning
confidence: 99%